Терракотовые статуэтки из раскопок Порфмия - Вахтина, М.Ю. (Боспорские исследования, 2010)
В статье дан обзор коллекции терракотовых статуэток, найденных при раскопках античного городища Порфмий в Восточном Крыму. За десятилетия раскопок этого памятника была собрана значительная коллекция статуэток и их обломков. В статті дан огляд колекцій теракотових статуеток, знайдених при розкопках античного городища Порфмій у Східному Криму. За десятиріччя розкопів цієї пам’ятки була зібрана значна колекція статуеток та їх уламків. The article deals with the collection of clay figurines, collected during the excavation of the city- site of Porthmion, situated in the Eastern Crimea. Many of them are of interest not only in terms of Greek art but also as evidence of religious practice at Porthmion at various times and places in the town and in its chora.